Celebrating differences while reserving commonality: work values of Chinese public organization employees. (9th September 2019) - Zhong, Wei; Bao, Yuanjie; Huang, Xianming
Abstract : While the profound and rapid changes currently occurring in China may influence and differentiate how work values are structured by employees working in different sectors, limited efforts have been made to address this issue. Drawing on institutional theory and the social psychological perspective, this study collects and analyzes data from Chinese public organization employees, to compare the work values of employees from the state sector, public sector, and state‐owned enterprise. The results reveal some noteworthy patterns in employee work values in each sector, and interesting similarities and differences in employee work values across sectors. This study contributes to the knowledge on employee work values in China by uncovering their characteristics in the broad institutional and organizational context. It also provides practical implications for the three sectors in China and for other developing and transition economies. Key points: It is possible and relevant to differentiate work value orientations among employees of the state sector, public sector and state‐owned enterprise (SOE). State sector employees were found to value prestigious work more than public sector and SOE employees. Public sector employees were found to value work that was consistent with their moral values more than state sector and SOE employees. SOE employees were found to be motivated more extrinsically at a general level than state sector and public sector employees. There were a number of commonalities in work values found for employees across sectors.